The Role of the Community in Minimizing Waste in the Tourism Environment at Pukan Beach, Bangka Belitung - Steven; Fadilah, Nurul; Sutoyo, Patricia Angelie (Politeknik Pariwisata NHI Bandung, 2024)
Waste is something that is familiar to the wider community. The problem related to waste that often occurs is careless disposal of waste, one of which is in public places in the form of tourist attractions, such as at Pukan Beach in Merawang District, Bangka Regency, Bangka Belitung Islands. Through research carried out using qualitative research methods by conducting interviews and observations, the results obtained were that the scattered rubbish was divided into two types, organic and inorganic and the cleaning process was quite difficult due to the lack of human resources and the large amount of rubbish scattered around. This is enough to make tourists feel uncomfortable because it makes the eyes unpleasant to see a beach area full of rubbish. Because of this, the role of participation from the community and the role of participation from visitors is needed. The role of the community must of course be more dominant in developing tourism spots in the area. With the participation of the community and visitors in maintaining the cleanliness of tourist attractions, sustainable tourism development can occur and provide substantial benefits for all communities, governments and the country.